2019
DOI: 10.1002/smll.201902699
|View full text |Cite
|
Sign up to set email alerts
|

Improved Biocompatibility of Amino‐Functionalized Graphene Oxide in Caenorhabditis elegans

Abstract: Graphene oxide (GO) holds high promise for diagnostic and therapeutic applications in nanomedicine but reportedly displays immunotoxicity, underlining the need for developing functionalized GO with improved biocompatibility. This study describes adverse effects of GO and amino‐functionalized GO (GONH2) during Caenorhabditis elegans development and ageing upon acute or chronic exposure. Chronic GO treatment throughout the C. elegans development causes decreased fecundity and a reduction of animal size, while ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 81 publications
4
15
1
1
Order By: Relevance
“…The results showed that higher concentrations of GO NPs induced more reproductive toxicity based on our experiments on brood size number in nematodes. Our results were consistent with most GO NP studies reporting that GO exposure can cause adverse effects through damaging the fertility and egg ejection behavior of nematodes (Kim et al, 2018;Rive et al, 2019, Wu et al, 2013Zhao et al, 2016b). Wu et al (2013) showed that C. elegans with prolonged exposure to 1-100 mg L -1 exhibited significantly decreased brood size compared to the control, but there were no significant between-group differences at 0.1 and 0.5 mg L -1 .…”
Section: Reproductive Toxicity Of Go Npssupporting
confidence: 92%
See 3 more Smart Citations
“…The results showed that higher concentrations of GO NPs induced more reproductive toxicity based on our experiments on brood size number in nematodes. Our results were consistent with most GO NP studies reporting that GO exposure can cause adverse effects through damaging the fertility and egg ejection behavior of nematodes (Kim et al, 2018;Rive et al, 2019, Wu et al, 2013Zhao et al, 2016b). Wu et al (2013) showed that C. elegans with prolonged exposure to 1-100 mg L -1 exhibited significantly decreased brood size compared to the control, but there were no significant between-group differences at 0.1 and 0.5 mg L -1 .…”
Section: Reproductive Toxicity Of Go Npssupporting
confidence: 92%
“…Kim et al (2018) revealed that accumulation of GO NPs (10 mg L -1 ) in the reproductive organs, which might be the direct cause of reproductive toxicity, could reduce brood size and sperm count by suppressing spermatogenesis of the hermaphrodite nematodes at the GO levels of 5 or 10 mg L -1 . However, the negative impact of GO NP exposure on the reproductive function in the present and published studies (Kim et al, 2018;Rive et al, 2019, Wu et al, 2013Zhao et al, 2016b), as well as our results, suggest that prolonged exposure to GO NPs at low doses from 0.0100 to 1.00 g L -1 could decrease progeny number or fecundity in N2 C elegans models.…”
Section: Accepted Manuscriptsupporting
confidence: 68%
See 2 more Smart Citations
“…[ 38 ] Some of the chemical properties include large surface area, diverse functionalities, and good biocompatibility. [ 8,39,40 ] These properties of GO allow it to be studied for several applications in nanomedicine, including bioimaging, biosensing and tissue regeneration. [ 41,42 ] However, the increasing use and large‐scale production of this material also necessitates careful investigations of its impact on human tissues.…”
Section: Figurementioning
confidence: 99%